PENGARUH FINANCIAL LITERACY, OVERCONFIDENCE, MODAL MINIMAL, PEMAHAMAN INVESTASI DAN RISIKO TERHADAP KEPUTUSAN INVESTASI DI PASAR MODAL (STUDI EMPIRIS MAHASISWA AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH METRO) - Astuti Astuti Anggraini; Yulita Zanaria; Sri Retnaning Rahayu (Universitas Muhammadiyah Metro, 2021)
This study aims to examine the factors that influence investment decisions in the capital market for accounting students at the Faculty of Economics and Business, Universitas Muhammadiyah Metro. The factors that influence investment decisions in the Capital Market are financial literacy, overconfidence, minimum capital, understanding of investment, and risks. This study uses a quantitative approach. The population in this study were 313 respondents. In this study, the sample technique used is nonprobability sampling with purposive sampling technique so that the sample obtained was 93 respondents. The data in this study were analysed using the assistance of the IBM SPSS version 20 program by testing multiple linear regression analysis. The results of this study indicate that financial literacy, overconfidence and minimal capital partially affect investment decisions in the capital market. Meanwhile, understanding investment and risk partially has no effect on investment decisions in the capital market. As well as financial literacy, overconfidence, minimal capital, understanding of investment and risk simultaneously affect investment decisions in the capital market.